A new species and typification in Pedicularis series Curvipes (Orobanchaceae) - Agnihotri, Priyanka; Husain, Danish; Sahoo, Dinabandhu; Barik, Saroj Kanta (Phytotaxa, 2018)
Pedicularis series Curvipes, of the family Orobanchaceae consisting of three species, is mainly distributed in eastern Himalaya, P. curvipes and P. nagaensis are found distributed from Sikkim to Manipur and P. amplicollis is reported from Bhutan. In the present study, a new taxon, closely related to P. amplicollis, is described from Dzükou valley, Manipur, and illustrated here as P. husainiana P.Agnihotri, D. Husain, D. Sahoo & S.K. Barik. Additionally, the lectotype of P. curvipes is designated here.